NISBIYLIK NAZARIYASI (Modern education and development, 2025)
• Albert Einstein 2.Klassik fizika 3 invariant. 4.inersial sanoq sistema. 5. Galileo Galiley 6.A.Michelson. 7.Hendrik Lorentz. 8.Henri Poinar